Surrounding risks - Mogens Steffensen (Risks, 2013)
Research in insurance and finance was always intersecting although they were originally and generally viewed as separate disciplines. Insurance is about transferring risks between parties such that the burdens of risks are borne by those who can. This makes insurance transactions a beneficial activity for the society. It calls on detection, modelling, valuation, and controlling of risks. One of the main sources of control is diversification of risks and in that respect it becomes an issue in itself to clarify diversifiability of risks. However, many diversifiable risks are not, by nature or by contract design, separable from non-diversifiable risks that are, on the other hand, sometimes traded in financial markets and sometimes not. A key observation is that the economic risk came before the insurance contract: Mother earth destroys and kills incidentally and mercilessly, but the uncertainty of economic consequences can be more or less cleverly distributed by the introduction of an insurance market.
Keywords: 330